The Implementation of the Core Tax System in Indonesia: A Systematic Literature Review - Karlinah, Lady; Sari, Hotma Glorya Ika; Sugondo, Liem Yan; Pratama, Irvan Bayu (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to systematically review the implementation of the Core Tax System in Indonesia as part of the national tax reform agenda. The research method employed is a Systematic Literature Review (SLR) by examining articles, reports, and relevant documents from various academic databases and official sources covering the period of 2018–2025. The literature selection process was conducted based on inclusion and exclusion criteria using the PRISMA approach (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), resulting in a set of studies analyzed thematically. The findings indicate that the implementation of the Core Tax System in Indonesia is shaped by four key themes: (1) technological readiness and digital infrastructure, (2) human resource capacity and competence, (3) regulatory and policy support, and (4) the impact on tax administration effectiveness and taxpayer compliance. While the system offers significant opportunities to enhance transparency and efficiency, the literature also highlights challenges such as limited digital literacy, resistance to change, and technical risks in the digitalization process. This study emphasizes that the success of the Core Tax System is determined not only by technical aspects but also by change management, public communication, and stakeholder engagement. The literature suggests several recommendations, including strengthening infrastructure, improving human resource capacity, and ensuring consistent policies to guarantee the sustainability of tax reform in Indonesia.